Development of Norms of Specific Physical Fitness Test for Male Cricket Players: Development of Norms for Physical Fitness Tests in Male Cricket Players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was to development of specific physical fitness norms for cricket players. The Study was delimited to 500 randomly selected state level male cricket players from central zone. Pull ups Test for measuring Arm Strength, Norms of Pull ups clearly shows that 100 points will be awarded to that subject who will score 36 or more Pull ups and 0 points will be awarded to that subject who will score 4 or less Pull ups. In Standing Broad Jump Test for measuring Leg Strength, Norms of Standing Broad Jump Test clearly shows that 100 points will be awarded to that subject who will jump 3.07 meter or more and 0 points will be awarded to that subject who will jump 1.87 meter or less. In Bent Knee Sit ups Test for measuring Abdominal Strength, Norms of Bent Knee Sit ups Test clearly shows that 100 points will be awarded to that subject who will score 72 or more Bent Knee Sit ups in one minute and 0 points will be awarded to that subject who will score 38 or less Bent Knee Sit ups in one minute. In 30 Meters Run Test for measuring Speed, Norms of 30 meters Run Test clearly shows that 100 points will be awarded to that subject who will runs 30 meters in 2.05seconds or less time and 0 points will be awarded that subject who will runs 30 meters in 8.85 seconds or more time. In Cooper 12 Minute Run Walk Test for measuring Aerobic Fitness, norms of Cooper 12 minute Run Walk Test clearly shows that 100 points will be awarded to that subject who will score 3170 meters or more and 1570 meters or less than, Subject will be awarded score 0 point will be awarded. In Phosphate Recovery Test for Measuring Balance and Coordination, Norms of Phosphate Recovery Test clearly shows that 100 points are awarded to a subject when he will manage to score 100 or more and 0 points are awarded when he will score 48 or less. In Bridge-Up Test for measuring Flexibility, Norms of Bridge-Up Test clearly shows that 100 points will be awarded to that subject who will score 25.30 or more and 0 points will be awarded to that subject who will score 7.30 or less. In Dodging Run Test for measuring Agility, Norms of Dodging Run Test clearly shows that 100 points will be awarded to that subject who will score 5.00 seconds or less time and 0 points will be awarded to that subject who will score 26.00 seconds or more time. In Six Second Dash Test for measuring Reaction Time Ability, Norms of Six Second Dash Test clearly shows that 100 points will be awarded to that subject who will score 73.80 meter or more and 0 points will be awarded that subject who will score 41.10 meter or less. In Bass Stick Test for measuring Balance and Coordination, Norms of Bass Stick Test clearly shows that 100 points will be awarded to that subject who will score 116 or more jumps in 15 seconds and 0 points will be awarded to that subject who will score 72 or less jumps in 15 seconds.